The possibility of using Internet marketing techniques in a scientific library - A. P. Kirjanova; N. S. Redkina (Библиосфера, 2013)
The essence, structure and advantages of using internet-marketing technologies are considered. The structure of marketing internet communication complex for the library marketing activity with the account of its non-profit specific character is proposed.